Miniature Design of 3D Printed Piston Cup Using PLA Filament Material in Manufactoring Process - G. A. PUTERO; M. Viqri; F. Risman; A.G. Dewantara (BIOMEJ, 2024)
The manufacturing process has evolved throughout the years, with the current existence of 3D printing methods revolutionizing the industry. In the world of manufacturing, 3D printing is essential for producing unique products through a computerized system that synchronizes with many parameters of the intended 3D printed product. The precision of the systems used in 3D printing eases the manufacturing process by displaying parameters of a product that can be thoroughly analyzed. Furthermore, the 3D printing computerized system is effective, energy-efficient, and reliable due to not having direct human involvement in the manufacturing process, thus reducing the percentage of human errors. CAD designs are used for 3D printing and can produce highly accurate 3D printed objects. Mechanical components, small objects, and CAD-accurate designs can easily be achieved through 3D printing. Additionally, 3D printing allows for the creation of miniatures with highly accurate reproductions, which is particularly valuable in industries such as aerospace, medical devices, and consumer electronics. These miniature creations can be manufactured with intricate details that were previously difficult or impossible to achieve with traditional methods. The capability to produce these detailed miniatures has opened new avenues for innovation and customization in manufacturing. Due to the many advantages and the high level of precision offered by 3D printing, many researchers are driven to continuously improve the technology. Advances in materials, printing speed, and resolution are continually being explored to expand the applications of 3D printing in various sectors. The potential for producing complex geometries and custom components on demand makes 3D printing a pivotal technology in the future of manufacturing.